2023
DOI: 10.1007/s11033-023-08336-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acids and a static magnetic field change the expression of transforming growth factor β isoforms in amelanotic melanoma cells

Abstract: Background Melanoma is an aggressive type of cancer that can metastasize to numerous other organs. TGFβ is one of the key signaling pathways in melanoma progression. Previous studies on various types of cancer have shown that both: polyphenols and a static magnetic field (SMF) can be potential chemopreventive/therapeutic agents. Therefore, the aim of the study was to evaluate the effect of a SMF and selected polyphenols on the transcriptional activity of TGFβ genes in melanoma cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Kimsa-Dudek et al [56] studied the effect of phenolic acids and a static magnetic field on the expression of TGF-β isoforms in amelanotic melanoma cells. They observed a significant decrease in the concentration of TGF-β1 and TGF-β2 proteins in cells treated with SMF and phenolic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Kimsa-Dudek et al [56] studied the effect of phenolic acids and a static magnetic field on the expression of TGF-β isoforms in amelanotic melanoma cells. They observed a significant decrease in the concentration of TGF-β1 and TGF-β2 proteins in cells treated with SMF and phenolic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid also significantly upregulated mRNA expression of the Casp3 and caspase-3 activity in C32 cells [216]. Later, they reported that both phenolic acids in the same melanoma cell line in combination with SMF decreased TGFβ protein levels [217]. Moreover, ChA in C32 cells suppressed the viability of melanoma cells and the expression of genes of antioxidant enzymes superoxide dismutase (SOD1, SOD2) and glutathione peroxidase (GPX1), as well as activity of SOD, GPx, and catalase (CAT).…”
Section: Phenolic Acidsmentioning
confidence: 93%